AnemiaScore: An Investigator-Developed Rule-Based Clinical Decision-Support Framework for Cancer-Related Anemia—A Single-Center Retrospective Proof-of-Concept Concordance Study - Antonio Macciò; Gianuario Sanna; Manuela Neri; Paolo Albino Ferrari (Diagnostics, 2026)
Background/Objectives: AnemiaScore is an investigator-developed, deterministic, rule-based clinical decision-support framework for cancer-related anemia. This initial proof-of-concept study evaluated agreement with recorded local oncologist decisions, used as a clinical reference comparator rather than an independent standard. Methods: This single-center retrospective study analyzed 180 directly comparable A–C cases in the primary three-category analysis. An exploratory full-cohort analysis included 188 eligible cases and descriptively incorporated Category D decisions arising either from the five-input laboratory core or from clinical factors outside that core. Results: In the primary cohort, overall percent agreement was 77.8% (140/180; 95% CI, 71.2–83.2%), Cohen’s κ was 0.637 (95% bootstrap CI, 0.537–0.731), and Gwet’s AC1 was 0.680 (95% bootstrap CI, 0.588–0.767). Among eight recorded clinician-override decisions, four met the laboratory-based R0 criterion, two were classified as Category D only through the external clinical-override classification, and two were not captured. The exploratory four-category agreement was 77.7% (146/188; 95% CI, 71.2–83.0%). Conclusions: AnemiaScore reproduced a substantial proportion of local decision patterns, but concordance does not establish therapeutic appropriateness, clinical efficacy, safety, or superiority. Prospective multicenter validation with independent review and clinical and patient-reported outcomes is required before routine use.